Can we enhance trust in the circular economy through referral marketing control? - Deborah Lacitignola; Angela Martiradonna (PLoS ONE, 2025)
Referral marketing can be considered a promising tool to support the transition toward a circular economy, thanks to its capacity to raise consumer awareness, foster loyalty and encourage participation in sustainable practices. However, to strengthen public trust in new circular business models, it becomes essential to manage such campaigns carefully. In this paper, we apply the Z-control method to regulate the dynamics of a referral marketing model with self-information, through control actions capable of influencing a campaign’s persistence and preventing its risk of collapse. Our focus is on two types of direct interventions: increasing the engagement of broadcasters and reducing consumer inertia. The analysis highlights how these marketing strategies must be applied over time in order for circular products, practices and behaviors to gain stable traction among the population. Reducing inertia, in particular, emerges as the more difficult challenge, suggesting that companies may need to adopt stronger marketing efforts while being mindful of how and when such efforts are applied. In this context, a non-monotonic application of marketing interventions over time appears especially important to avoid overwhelming consumers early on and to better address the psychological resistance often linked to inertia.